2022
DOI: 10.1002/hed.27170
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐modified Glasgow prognostic score: A new prognostic marker for head and neck cancer

Abstract: Background The modified Glasgow prognostic score (mGPS) includes C‐reactive protein and serum albumin levels and is a useful prognostic tool for malignant tumors. The immune system affects cancer progression and recurrence and treatment response. We hypothesized that increasing the lymphocyte count improves mGPS, and we created a new prognostic marker termed immune‐mGPS (imGPS). Methods This study included 461 patients with head and neck squamous cell carcinoma (HNSCC). The imGPS was calculated as the conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Terazawa et al studied head and neck cancer patients and found a significant relationship between survival, low albumin, and high CRP. However, mGPS failed to predict poor prognosis in this patient group [10]. Siyu et al reported that GPS and mGPS could act as poor prognostic indicators in patients with ovarian cancer [11].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Terazawa et al studied head and neck cancer patients and found a significant relationship between survival, low albumin, and high CRP. However, mGPS failed to predict poor prognosis in this patient group [10]. Siyu et al reported that GPS and mGPS could act as poor prognostic indicators in patients with ovarian cancer [11].…”
Section: Discussionmentioning
confidence: 74%
“…Like CAR, GPS and mGPS have been assessed as inflammation markers, especially in patients with malignancies [10][11][12]. Terazawa et al studied head and neck cancer patients and found a significant relationship between survival, low albumin, and high CRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that imGPS offers better accuracy than mGPS in predicting the evolution of patients with HNSCC. mGPS is considered a precise predictor of OS for patients with HNC and after analyzing the data of the study carried out at the University of Tsukuba Hospital including 210 cases of HNC, values of 1 and 2 of the score are associated with worst outcomes (23).…”
Section: Discussionmentioning
confidence: 99%
“…a useful prognostic tool for malignant tumors. [6,7] The mGPS correlates with clinical outcomes in patients with head and neck cancers [27]. High CAR predicts early recurrence and poor prognosis in patients with gastric cancer with curative intent.…”
mentioning
confidence: 99%